PERPUTARAN MODAL KERJA, PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN DAN LIKUIDITAS PENGARUHNYA TERHADAP PROFITABILITAS (STUDI KASUS PADA BURSA EFEK INDONESIA PERIODE 2016-2018) - Ulfa, Triyas Umi; Wahyu W, Listyorini (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2020)
This  research  analyzes  the  effect  of   Working  Capital  Turnover,  Growth,  Size  and  Liquidity  on  Profitability  (Study  at  Manufacture  Companies  listed  on  the  Indonesia  Stock  Exchange  for  the  2016-2018  period).  There  are  population  of  143  Manufacture  Companies  listed  on  the   Indonesia  Stock  Exchange.  The  sample  selection  method  uses  purposive  sampling  which  is  based  on  predetermined  criteria,  then  obtained  total  sample  are  44  manufacture  companies  during  2016-2018  period. The  analytical  tool  use  is  multiple  linear  regression  .  The  results  this  research  show  that  working  capital  turnover  and  growth  have not  effect  on  profitability,  while  size  and  liquidity  have effect on profitability.  Keywords : Working  Capital  Turnover,  Growth,  Size,  Liquidity,  Profitability